(untitled) (Transport systems and technologies, 2018)
The article discusses issues related to the reasons for the loss of performance of a hydraulic damper of a passenger car of the НЦ-1100 type when a failure occurs in the sealing cups, and proposes ways to improve the tightness of the damping device. In the ―Universal Mechanism‖ [1, 9] program complex, using a built-in computer model of the dynamics of a passenger car on КВЗ-ЦНИИ bogies, vertical forces are transmitted to the oscillation damper rod under conditions close to operational ones. Using the software MSC.Marc / Mentat (MSC Software, USA), a study of the stress-strain state of a typical rubber cuff under external loads was conducted. The distribution of changes in contact pressure at the point of connection of the stem with the cuff is determined depending on the ratio of the pressure of the working fluid and the calculated total pressure due to the elastic properties of rubber and the action of the ring spring. Long-lasting work and reliability of the cuff are primarily determined by the selection of the contact pressure of the coupling pair with minimum values of frictional effects (friction, relaxation of stresses). At the pressure of the working body, the contact pressure depends on the physical and mechanical properties of the elastic part of the cuff, its initial deformation, the radial force of the spring, and the design performance. With insufficient contact pressure there is a risk of a loss of working fluid, and more than normalized pressure leads to an increase in the temperature in the contact area, and, accordingly, to reduce the elastic properties of the material cuff, which reduces the life of its work.